Rapid and sensitive analysis of mRNA polyadenylation states by PCR. - Sallés, F J; Strickland, S (Genome Research, 1995)
A rapid and sensitive technique is described that measures the length of the poly(A) tail on a specific mRNA within subnanogram quantities of total cellular RNA [the Poly(A) test (PAT)]. In a single-tube reaction, a poly(dT) primer is synthesized in situ on the poly(A) tail of mRNAs using oligo(dT) and DNA ligase. By modulating the annealing temperature and primer concentrations, a GC-rich adapter sequence is targeted to the 5' end of the poly(dT) primer. This ligated poly(dT)-anchor is then used to prime reverse transcription of the mRNA, yielding a library of PAT cDNAs. The length of a poly(A) tail is determined by PCR amplification using the oligo(dT)-anchor primer and a message-specific primer. Comparison of PCR products from different samples allows quantitative determination of changes in polyadenylation of a given mRNA. This technique overcomes many of the pitfalls associated with conventional poly(A) tail length assessments and should prove useful in studying a variety of processes relating to polyadenylation.